1990
DOI: 10.1007/bf01437170
|View full text |Cite
|
Sign up to set email alerts
|

Sternheimer free determination of the47Ti nuclear quadrupole moment from hyperfine structure measurements

Abstract: The hyperfine structure (hfs) of 12 metastable states of 47Ti ihas been measured by laser induced fluorescence. 11 of these states have been measured additionally very precisely by a laser-rf double resonance method. Taking into account results of earlier hfs measurements, the hfs of altogether 17 fine structure states has been analyzed by the simultaneous parametrization of the one-and two-body interactions in the atomic hfs for the model space (3d+4s) N÷2 (N=2). This gives 16 parameters for the magnetic dipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
5

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 20 publications
0
60
0
5
Order By: Relevance
“…We therefore use the experimental values for the relevant isotope where available, but use rescaled experimental data from the other where it does not exist for both isotopes. Data on hyperfine structure for the Ti  lines for which we have isotopic information are best obtained from Gangrsky et al (1995) and Aydin et al (1990). In cases of overlap, the ABMR data of Aydin et al have smaller uncertainties than those of Johann et al (1981), whereas the LFS data of Gangrsky et al is preferable to Aydin et al's LFS.…”
Section: Isotopic and Hyperfine Structurementioning
confidence: 93%
See 1 more Smart Citation
“…We therefore use the experimental values for the relevant isotope where available, but use rescaled experimental data from the other where it does not exist for both isotopes. Data on hyperfine structure for the Ti  lines for which we have isotopic information are best obtained from Gangrsky et al (1995) and Aydin et al (1990). In cases of overlap, the ABMR data of Aydin et al have smaller uncertainties than those of Johann et al (1981), whereas the LFS data of Gangrsky et al is preferable to Aydin et al's LFS.…”
Section: Isotopic and Hyperfine Structurementioning
confidence: 93%
“…It has been consistently found that the hyperfine A constants for 47 Ti and 49 Ti are essentially equal, and B(47)/B(49) ≈ 1.22, for all levels (Channappa & Pendlebury 1965;Aydin et al 1990;Stachowska et al 1994;Gangrsky et al 1995). We therefore use the experimental values for the relevant isotope where available, but use rescaled experimental data from the other where it does not exist for both isotopes.…”
Section: Isotopic and Hyperfine Structurementioning
confidence: 99%
“…relative to Ti I [14] and Ti II [7]. Since these ratios are very close for these two neighbour elements in the Periodic Table, we can conclude that the deduced ( ) In Table 7 we have listed the measured hfs constants A given in MHz, used in our fitting procedure.…”
Section: Accurate Fine and Hyperfine Structure Analysismentioning
confidence: 66%
“…Later, in 1985, Dembczyński [25] elaborated a new parametrization method which took into account simultaneously one-and two-body interactions in atomic hfs structure of the configurations (3d+4s) N +2 . This method was applied to the interpretation of iron, vanadium, titanium and cobalt atoms [26][27][28][29]. In the following years, the above mentioned method of parametrization of interactions in the hfs was extended up to three open electronic shells [6,30].…”
Section: Electrostatically Correlated Hyperfine Interactions (Chfs)mentioning
confidence: 99%